The impact of climate change on a particular region or country - Singh, Dr. Vikram (Innovative Research Thoughts, 2020)
The problem known as climate change is a global one that has repercussions in every region of the planet in a variety of different ways. But the effects of climate change will be different in different parts of the world. In this abstract, we are going to talk about the effects that climate change has had on a certain nation or area. The Arctic is a place that is a good illustration of one that is being badly impacted by climate change. The Arctic area is now seeing the quickest rate of warming of any other place on the planet. Because of this, the sea ice in the Arctic is disappearing at a pace that has never been seen before, with a decline of around 13.1% every decade between 1979 and 2018. Because to the melting of the sea ice, there has been an increase in the level of the water, which is having an effect on the infrastructure and communities along the shore. The melting of the Arctic sea ice is causing changes in ocean currents, which can lead to altered weather patterns, including more frequent extreme weather events such as heat waves, droughts, and floods. The melting of the Arctic sea ice is also causing an increase in the amount of sunlight that reaches the Earth's surface. These changes are having an effect not just on humans but also on animals, such as polar bears, who are seeing their habitat disappear as a result of the melting sea ice. One such illustration of this would be the effect that climate change has had on the nation of Bangladesh. Because of its position in the delta formed by the Ganges, Brahmaputra, and Meghna rivers, Bangladesh is one of the nations that is most susceptible to the effects that climate change will have. The United States is now seeing an increase in the number of floods, cyclones, and other types of severe weather, as well as their severity. These occurrences are inflicting major damage to infrastructure, property, and crops, which ultimately results in economic losses and an uncertain supply of food. In addition, the elevation of the sea level is allowing saltwater to seep into freshwater sources, which makes it more difficult for people to get potable water.